Group Membership and Social Identities in a Formative Intervention in a Mexican Hospital - Brito Rivera, Hugo Armando; Alby, Francesca; Zucchermaglio, Cristina (Frontiers in Psychology, 2021)
Formative intervention is a participatory methodology that supports organizational change by means of an interactive and systematic dialogue carried out by researchers and participants. In this process the researchers contribute to expand the conversational space in the organization by supporting participants in examining and reflecting on their own work practices, as well as in modelling, shaping and experimenting with innovations. Drawing on transcripts of videotaped sessions, this article analyzes how change is discursively sustained by the researchers who conduct the meetings within a formative intervention in a Mexican hospital. The quantitative and qualitative analysis focuses on the collective pronoun “we” as membership categorization device deployed by the researchers for rhetorical and pragmatical aims, such as questioning about the state of necessity for the intervention, engaging the participants, or introducing a proposal of innovation with the participants. Results show how group membership and social identity markers are used by researchers to support emerging forms of collaboration, participants’ involvement and creation of common ground during the intervention process. In terms of the practical implications of the study, an informed and strategic use of membership categorization devices by the researcher can increase the effectiveness of their formative and expansive role.